Improvement of Mold Material for Casting Thin-Walled Details from Gray Cast Iron - Jamshidbek Khasanov; Nodir Turakhodjaev; Fakhriddin Makhmudov (Research Parks Publishing LLC, 2022)
In this article, in the casting of thin-walled parts from gray cast iron, along with the mechanical, technological, physical properties of the mold material, it is important that the mold responds to technical and economic students.